2013
DOI: 10.7567/apex.6.062103
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence from InN Nanorod Arrays with a Critical Size

Abstract: In this report, we investigated the rod size dependence of photoluminescence (PL) from vertically aligned indium nitride (InN) nanorod arrays grown on Si(111) substrates. Abnormal temperature dependence of the PL peak energy and the PL bandwidth was observed for InN nanorods with a critical diameter, which is of the same order of the surface electron accumulation layer (20 nm). Exceptionally large activation energy of the nanorods with the critical diameter implies that holes within these narrow nanorods need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…We estimate the binding energy of these acceptor like centers to be 40 meV, in rather good agreement with the value of 31 ± 1.5 meV determined through PL experiments as a function of temperature. Our experimental observation is also very close to previously reported experimental values in the range of ~ 25-50 meV, which are associated to impurities [24], [25] . The n concentration deduced from the analysis of the low temperature spectrum related to the sample grown at 660 °C is about 2.6 x 10 18 cm -3 .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…We estimate the binding energy of these acceptor like centers to be 40 meV, in rather good agreement with the value of 31 ± 1.5 meV determined through PL experiments as a function of temperature. Our experimental observation is also very close to previously reported experimental values in the range of ~ 25-50 meV, which are associated to impurities [24], [25] . The n concentration deduced from the analysis of the low temperature spectrum related to the sample grown at 660 °C is about 2.6 x 10 18 cm -3 .…”
Section: Resultssupporting
confidence: 92%
“…Segura-Ruiz et al have shown that the effect of the surface electron accumulation layer on the optical band gap of InN nanocolumn grown by MBE is more pronounced when the diameter decreases [25] . Ahn et al have revisited these findings through a detailed study comparing the optical properties of InN film and nanorods with different diameters [24] . This may explain, in part, the high peak energy of 0.85 eV recorded from the InN nanorods grown at 610 °C, which present small diameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the III-nitrides, InN has the smallest band gap and effective electron mass [11,12,43], which is attractive for high-frequency electronic devices, near-infrared optoelectronics, and high-efficiency solar cells [44]. Moreover, because of the high intrinsic surface donor density, InN is considered as a very promising material for highly sensitive detection of ions, gases, vapors, and liquids [45,46,47,48].…”
Section: Introductionmentioning
confidence: 99%